Complement C3 inhibitor in patients with paroxysmal nocturnal hemoglobinuria with suboptimal response to C5 inhibitor therapy - M. V. Marchenko; O. U. Klimova; E. V. Anikina; A. V. Lapina; T. A. Rudakova; T. I. Ksenzova; A. D. Kulagin (Онкогематология, 2024)
The introduction of the complement component C5 inhibitor eculizumab has radically changed the prognosis and quality of life of patients with paroxysmal nocturnal hemoglobinuria. Up to 30 % of patients develop only a suboptimal response to C5 inhibition. One reason for this is activation of extravascular hemolysis, due to opsonization of erythrocytes with fragments of the C3 component. Pegcetacoplan, the first ever registered C3 inhibitor, is aimed at solving this problem.In Russia, 2 patients received pegcetacoplan as part of a phase 3, randomized, open-label, active-comparator controlled trial PEGASUS. The analysis includes data from the first year of therapy: the run-in period (pegcetacoplan 1080 mg SC twice weekly in addition to the current dose of eculizumab, 4 weeks), the randomized controlled period (both patients were randomized to eculizumab monotherapy, 16 weeks), and the open-label period of pegcetacoplan therapy (32 weeks). Data from the extension study to evaluate the long-term safety and efficacy of pegcetacoplan are also presented. The duration of follow-up on pegcetacoplan therapy in both patients exceeded 4 years.